Crop establishment and weed control options for sustaining dry direct seeded rice production in Eastern India - Saha, Sanjoy; Munda, Sushmita; Singh, Sudhanshu; Kumar, Virender; Jangde, Hemant Kumar; Mahapatra, Ashirbachan; Chauhan, Bhagirath S. (MDPI, 2021)
Dry direct seeded rice (DSR) has emerged as an economically viable alternative to puddled transplanted rice to address emerging constraints of labor and water scarcity and the rising cost of cultivation. However, wide adoption of DSR is seriously constrained by weed management trade-off. Therefore, the availability of effective weed control options is critical for the success and wide-scale adoption of DSR. A field study was conducted at ICAR-National Rice Research Institute, Cuttack, India, in the dry seasons of 2015 and 2016 to evaluate the performance of three crop establishment methods and five weed control practices on weed management, productivity, profitability and energetics of dry DSR. The results demonstrated that weed density and weed dry weight was lower in drill seeding than broadcast seeding by 26–36% and manual line-seeding by 16–24%, respectively, at 30 and 60 days after crop emergence (DAE). Among herbicides, post-emergence application (17 DAE) of azimsulfuron was most effective in controlling weeds compared to early post application of bispyribac-sodium and bensulfuron-methyl+pretilachlor. Weed competition in the weedy check treatment resulted 58% reduction in rice yield. Among establishment methods, drill-seeding was most profitable with US $ 685 ha−1 higher net income than broadcast seeding primarily due to higher yield. Among weed control treatments, azimsulfuron was most profitable resulting in US $ 160 and 736 ha−1 higher net income than weed free and weedy check, respectively. The specific energy was lowest for drill seeding among establishment method and azimsulfuron among weed control practices, suggesting lowest energy consumed in producing per unit of grain yield.